The normal and pathological language - Espejo, Luis D. (1920)
Language disorders are an important chapter to the doctor and psychologist, for his analytical study contributes to a better understanding of the mechanism of intelligence; in a way it is a pathological study method function. The multiplicity of clinical aspects provides speech pathology, the uncertainty about the precise location of the various centers of the word, the existence of clinical appearance similar types related to different injuries and pathological characters topography; this set of reasons do not, at present, make an anatomical classification, rigorously scientific, and force simply list the different forms depending on their dynamic alteration.